Associations Between 24-Hour Time Use and Academic Achievement in Australian Primary School–Aged Children. (December 2020) - Watson, Amanda; Dumuid, Dorothea; Olds, Tim
Background: Previous research has examined associations between individual activity behaviors and academic achievement. Yet activity behaviors should be analyzed together because they are codependent parts of the 24-hour day. Aims: This study aims to explore the associations between all daily activity behaviors (sleep, sedentary time, light physical activity [LPA], and moderate-to-vigorous physical activity [MVPA]) and academic achievement using compositional data analysis. Method: Participants for this study were drawn from two cohorts: the Australian arm of the cross-sectional International Study of Childhood Obesity, Lifestyle and the Environment ( n = 452; mean age 10.7 years ( SD = 0.4); 54% female) and CheckPoint ( n = 1278; mean age 12 years [ SD = 0.4]; 50% female), a cross-sectional study nested between Waves 6 and 7 of the Longitudinal Study of Australian Children. Objective daily activity behavior data (sleep, sedentary time, LPA, and MVPA) were collected using 8-day, 24-hour accelerometry. Academic achievement was assessed using a nationally administered standardized test in literacy (spelling, grammar and punctuation, writing and reading) and numeracy. Compositional models (adjusted for age, sex, socioeconomic position, and pubertal development) regressed academic scores against isometric log ratios of activity behaviors. We used the models to estimate academic achievement for observed daily activity mixes. Estimated outcomes were plotted against time spent in each individual activity domain, and loess curves were fitted. Discussion and conclusion: In two different cohorts using two different accelerometers, lower LPA was related to better numeracy and literacy and higher sedentary time to better literacy (relative to time spent in other domains). Discussion and conclusion . LPA likely "drains time" from other movement behaviors, which are beneficial for academic achievement.